2013
DOI: 10.1007/s12028-013-9927-x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Hypothermia Reduces Middle Cerebral Artery Flow Velocity in Patients with Severe Aneurysmal Subarachnoid Hemorrhage

Abstract: Background: Transcranial Doppler (TCD) is widely used to detect and follow up cerebral vasospasm after sub-arachnoid hemorrhage (SAH). Therapeutic hypothermia might influence blood flow velocities assessed by TCD. The aim of the study was to evaluate the effect of hypo-thermia on Doppler blood flow velocity after SAH. Methods: In 20 patients treated with hypothermia (33°) due to refractory intracranial hypertension or delayed cerebral ischemia (DCI), mean flow velocity of the middle cerebral artery (MFVMCA) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…As previously suggested, TH mediates its neuroprotective effects by modulations of molecular, metabolic and inflammatory processes, possibly supporting associations with cerebral blood flow velocities [6,12,[28][29][30] . Such a mechanistic association of TH seems likely, yet its influence on actual peak spasm and its clinical significance warrant further investigations [31] . Available clinical studies have investigated TH rather as acute treatment strategy for increased ICP than for its effects on vasospasm and DCI [12-14, 29, 31] .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As previously suggested, TH mediates its neuroprotective effects by modulations of molecular, metabolic and inflammatory processes, possibly supporting associations with cerebral blood flow velocities [6,12,[28][29][30] . Such a mechanistic association of TH seems likely, yet its influence on actual peak spasm and its clinical significance warrant further investigations [31] . Available clinical studies have investigated TH rather as acute treatment strategy for increased ICP than for its effects on vasospasm and DCI [12-14, 29, 31] .…”
Section: Discussionmentioning
confidence: 96%
“…Reported macrovascular spasm rate may be exaggerated as low Doppler thresholds were applied and hypothermia itself may reduce cerebral blood flow limiting the interpretation of Doppler-based results but reinforce the positive associations of TH for DCI and functional outcome [23,31] . Within this study, DCI rate was very high as DCI detection was based exclusively on CT findings rather than on apparent neurologic deficits or multimodal imaging since assessment and executability in critically ill, mechanically ventilated SAH patients are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence from animal studies that therapeutic hypothermia may reduce secondary brain injury and the risk of cerebral vasospasm, hypothermia during aneurysm surgery has failed to demonstrate a clinical benefit [25]. One recent study examined Doppler middle cerebral artery (MCA) blood flow after induction of therapeutic hypothermia (33°, on average 5 days after SAH) in patients with increased intracranial pressure or DCI [25]. The authors demonstrated that therapeutic hypothermia resulted in decreased MCA blood flow, suggesting that therapeutic hypothermia may be useful for select patients.…”
Section: Improving Neurological Outcomes After Subarachnoid Hemorrhagementioning
confidence: 99%
“…A few very interesting randomized trials are currently investigating neurocritical care measures beyond neurosurgery in or including SAH: EARLYDRAIN on early lumbar drainage combined with EVD [9], SETPOINT2 on early tracheostomy [10], NEWTON on slow-release nimodipine via EVD [11], ULTRA on early tranexamic acid [12], and HIMALAIA on induced hypertension [13]. However, there are so many other NCCU aspects to be addressed prospectively: level of sedation, modes of ventilation [14,15], cardiopulmonary stability [16,17], monitoring-based circulatory strategies [18], temperature control [19][20][21], delirium management, the nursing factor and mobilization, policies of do-not-resuscitate orders and withdrawal of care [22,23], and many other day-to-day care decisions that may substantially impact outcome. Particularly, the poor-grade SAH patient, prone to so many cerebral and systemic complications, may benefit from aggressive surveillance, superb nursing care, and close clinical monitoring.…”
mentioning
confidence: 99%